Dinâmica Institucional, Políticas Públicas e o Desempenho Político Ambiental Brasileiro (Sustainability in Debate, 2011)
IThis research investigated the effects of the interdependence between politicalinstitutions and development models in the performance of environmental policiesin Brazil. The central hypothesis of this work is that given the interdependencebetween the organizations responsible for environmental policies and developmentpatterns somewhat responsive to environmental complexity, there is a dispersionof decision-making model for encouraging the development of high-carbon. Inaddition to literature review in Ecological Economics and Public Policy, were putinto operation (1) an analysis of brazilian political-institutional design, and (2)the public expenditure framework of the Brazilian federal government with theenvironment. Two results were observed: first) the design and the powers of theinstitutions responsible for policy formulation and implementation of public policiesinterfere with the efficiency of environmental policies; second) the higher theinstitutional openness, the greater the tendency of decision-making paralysis inthe formulation and implementation of environmental public policies.